OPTIMASI KUAT TEKAN DAN PENYERAPAN AIR PAVING BLOCK MENGGUNAKAN AKS ADDITIVE - Mulyati, Mulyati; Nurul Fausi, Muhammad (ITP Press, 2023)
This study used AKS additive as an added ingredient for the mixture for making paving blocks. The purpose of this study was to determine the optimum value of the compressive strength and water absorption of paving blocks from the addition of AKS additive into the mixed ingredients for making paving blocks. The ratio of a mixture of cement and sand in the manufacture of paving blocks is used 1: 3, and the addition of AKS additives is 0%, 1.6%, 1.7%, 1.8%, 1.9% and 2.0% by weight of cement. The paving block test object used a mold with a size of 20 cm x 10 cm x 6 cm. Testing of the compressive strength and water absorption of paving blocks was carried out at 28 days of age. The results of the study using AKS additive as an added ingredient in the mixture for making paving blocks can increase compressive strength and reduce water absorption. The highest average compressive strength of 12.67 MPa and the lowest average water absorption of 7.06% was obtained by using 1.9% AKS additive, meeting the requirements for quality C paving blocks used for sidewalks or pedestrians.